Dietary Patterns of Women Are Associated with Incident Abdominal Obesity but Not Metabolic Syndrome(2) - Kimokoti, Ruth W. (American Society for Nutrition, 2012)
Data on the relationship between empirical dietary patterns and metabolic syndrome (MetS) and its components in prospective study designs are limited. In addition, demographic and lifestyle determinants of MetS may modify the association between dietary patterns and the syndrome. We prospectively examined the relationship between empirically derived patterns and MetS and MetS components among 1146 women in the Framingham Offspring/Spouse cohort. They were aged 25–77 y with BMI ≥18.5 kg/m(2) and free of cardiovascular disease, diabetes, cancer, and MetS at baseline, and followed for a mean of 7 y. Five dietary patterns, Heart Healthier, Lighter Eating, Wine and Moderate Eating, Higher Fat, and Empty Calorie, were previously identified using cluster analysis from food intake collected using a FFQ. After adjusting for potential confounders, we observed lower odds for abdominal obesity for Higher Fat [OR = 0.48 (95% CI: 0.25, 0.91)] and Wine and Moderate Eating clusters [OR = 0.28 (95% CI: 0.11, 0.72)] compared with the Empty Calorie cluster. Additional adjustment for BMI somewhat attenuated these OR [Higher Fat OR = 0.52 (95% CI: 0.27, 1.00); Wine and Moderate Eating OR = 0.34 (95% CI: 0.13, 0.89)]. None of the clusters was associated with MetS or other MetS components. Baseline smoking status and age did not modify the relation between dietary patterns and MetS. The Higher Fat and Wine and Moderate Eating patterns showed an inverse association with abdominal obesity; certain foods might be targeted in these habitual patterns to achieve optimal dietary patterns for MetS prevention.